Carreadores lipídicos nanoestruturados para incorporação de complexos de cobre(ii) aplicáveis no estudo frente ao Mycobacterium tuberculosis - Sato, Mariana Rillo [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Tuberculosis (TB) is known worldwide as the leading infectious disease of chronic evolution in which the abandonment of treatment before the recommended period tends to cause the development of more severe disease, such as the appearance of resistant strains. Copper interacts with biologically active ligands developing copper(II) complex with activities antimicrobial. Nanostructured lipid carriers (NLCs) have gained prominence in the pharmaceutical field, since they have the ability to compartmentalize efficiently lipophilic drugs and modify their properties and behavior in the biological environment. The aims of this study was to evaluate the potential of copper(II) complexes-loaded NLCs applicable in the study against Mycobacterium tuberculosis. Copper(II) complexes containing isoniazid binder were obtained and they were entitled C1, C2, and C3 where they have co-binders anionic chloride, cyanate and thiocyanate, respectively. NLCs were obtained by fusion-emulsification technique, formulations were obtained by Ultra turrax at 5000 rpm for 10 minutes followed by sonicator at 8% amplitude for 20 minutes to obtain stable NLCs, those were incorporated of 3.50% and 0.50% to surfactant poloxamer 407 and cetrimonium bromide, respectively, and 2.07%, 2.50% and 0.88% of polyoxyethylene stearate lipids, triglycerides of capric acid/caprylic and ethoxylated hydrogenated castor oil 40 OE (F32) or castor oil (F38), respectively. Copper(II) complexes were incorporated into NLCs (F32.OE.C1, F32.OE.C2, F32.OE.C3 and F38.OR.C1, F38.OR.C2, F38.OR.C3) and characterized by diameter (Dmn) , polydispersivity index (PDI) and zeta potential (ZP) for 1, 15, 30, 45 and 60 days, which revealed homogeneous dispersion and excellent physical stability over the same period; the atomic force microscopy confirmed that developed NLCs are spherical particles dispersions at nanometer scales; differential scanning calorimetry revealed that the constituents used in the formulations interacted in the systems and confirmed that copper(II) complexes were incorporated in the NLCs. The antimicrobial activity of the complexes against M. tuberculosis H37Rv was determined by the resazurin microdilution assay demonstrated potential anti-TB when complexes were incorporated into NLCs. Cytotoxicity assay in murine macrophage-like cells J774A.1 (ATCC TIB-67) e MRC-5 (ATCC-CCL-171) for 24 h and acute toxicity of the complex against Artemia salina L (Artemiidae) showed the formulations have toxicity in all tested concentrations; although published reports indicated the safety of the components used of the formulations, studies should be conducted in animal models to assess the acute toxicity. These results suggest that NLCs have potential application in the study against Mycobacterium tuberculosis.

A Tuberculose (TB) é mundialmente conhecida como a principal doença infecto-contagiosa de evolução crônica, em que o abandono do tratamento antes do período recomendado tende a ocasionar o desenvolvimento de casos mais graves da doença, gerando o aparecimento de cepas resistentes. O cobre interage com ligantes biologicamente ativos desenvolvendo complexos de cobre(II) com ações antimicrobiana. Carreadores lipídicos nanoestruturados (CLNs) vêm se destacando na área farmacêutica, pois apresentam a capacidade de compartimentalizar, de maneira eficiente fármacos lipofílicos e de modificar suas propriedades e comportamento em meio biológico. O objetivo deste trabalho foi avaliar o potencial de CLNs acrescidos de complexos de cobre(II) aplicáveis no estudo frente ao Mycobacterium tuberculosis. Foram obtidos 3 complexos de cobre(II), intitulados C1, C2 e C3 que contem o ligante isoniazida e os co-ligantes aniônicos cloreto, tiocianato e cianato, respectivamente. Os CLNs foram obtidos pela técnica de fusão-emulsificação, testando-se diversas formulações por Ultra turrax a 5000 rpm por 10 minutos e por sonicador com amplitude 8% por 20 minutos até a obtenção de CLNs estáveis, que foram constituídos de 3,50% e 0,50 % de poloxamer 407 e brometo de cetrimônio, respectivamente, e de 2,07%, 2,50% e 0,88% de estearato de polioxietileno, triglicérides do ácido cáprico/caprílico e óleo de rícino hidrogenado e etoxilado 40 (F32) ou óleo de rícino (F38), respectivamente. Os complexos de cobre(II) foram incorporados nos CLNs (F32.OE.C1, F32.OE.C2, F32.OE.C3, e F38.OR.C1, F38.OR.C2, F38.OR.C3), e caracterizados por diâmetro hidrodinâmico médio (Dnm), índice de polidispersidade (IPD) e potencial zeta (PZ) por 1, 15, 30, 45 e 60 dias, revelando homogeneidade da dispersão e excelente estabilidade física; a microscopia de força atômica confirmou que os CLNs tratam-se de dispersões de partículas esféricas em escalas nanométricas; a calorimetria exploratória diferencial revelou que os componentes utilizados nas formulações interagiram para formação do sistema e que os complexos de cobre(II) foram incorporados nos CLNs. A atividade antimicrobiana dos complexos, frente ao M. tuberculosis H37Rv determinada pelo ensaio de microdiluição com Resazurina evidenciaram potencialização da ação anti-TB pela incorporação dos complexos nos CLNs. Os ensaios de citotoxicidade frente à linhagem de macrófagos J774A.1 (ATCC TIB-67) e de MRC-5 (ATCC-CCL-171) em 24 h e a toxicidade aguda dos complexos frente à Artemia salina L., mostraram que as formulações apresentaram toxicidade em todas as concentrações testadas; apesar de relatos da literatura indicarem a segurança dos componentes das formulações, estudos devem ser realizados em modelos animais para avaliar a toxicidade aguda. Os resultados sugerem que os CLNs apresentam aplicação potencial no estudo frente ao Mycobacterium tuberculosis.
Nanostrutured lipid carriers to incorporation for copper(ii) complex applicable in the study against Mycobacterium tuberculosis
Keywords: Citotoxicidade; Tuberculose; Complexos de cobre(II); Carreadores lipídicos nanoestruturados; Tuberculosis. Copper(II) complex; Nanostructured lipid carriers; Cytotoxicity